Regioselectivity of Lipase-Catalysed Deacetylation of Methyl 2,3,5-tri-OAcetyl-α, β-D-Furanosides in Ionic Liquid - Gudino, Esteban D. (2012)
Ionic liquids (ILs) were assayed as reaction medium for the enzymatic deacetylation of three methyl 2,3,5-tri-O-acetyl-a,b-D-furanosides and the obtained results show the influence of the IL and the furanose structure on the regioselectivity of hydrolyses catalysed by the tested lipases. In a reaction medium consisting of a 1:1 mixture of 30 mM phosphate buffer (pH 7) and 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]), Candida rugosa lipase catalysed the formation of methyl 2,3-di-O-acetyl-a,b-D-arabinofuranoside in 77 %, while in a 9:1 mixture of the same buffer and 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4]), methyl 2,3-di-O-acetyl-a,b-D-ribofuranoside was obtained in 62 %.